Protection of the Ovine Fetal Gut against Ureaplasma-Induced Chorioamnionitis: A Potential Role for Plant Sterols - van Gorp, Charlotte (Nutrients, 2019)
Chorioamnionitis, clinically most frequently associated with Ureaplasma, is linked to intestinal inflammation and subsequent gut injury. No treatment is available to prevent chorioamnionitis-driven adverse intestinal outcomes. Evidence is increasing that plant sterols possess immune-modulatory properties. Therefore, we investigated the potential therapeutic effects of plant sterols in lambs intra-amniotically (IA) exposed to Ureaplasma. Fetal lambs were IA exposed to Ureaplasma parvum (U. parvum, UP) for six days from 127 d–133 d of gestational age (GA). The plant sterols β-sitosterol and campesterol, dissolved with β-cyclodextrin (carrier), were given IA every two days from 122 d–131 d GA. Fetal circulatory cytokine levels, gut inflammation, intestinal injury, enterocyte maturation, and mucosal phospholipid and bile acid profiles were measured at 133 d GA (term 150 d). IA plant sterol administration blocked a fetal inflammatory response syndrome. Plant sterols reduced intestinal accumulation of proinflammatory phospholipids and tended to prevent mucosal myeloperoxidase-positive (MPO) cell influx, indicating an inhibition of gut inflammation. IA administration of plant sterols and carrier diminished intestinal mucosal damage, stimulated maturation of the immature epithelium, and partially prevented U. parvum-driven reduction of mucosal bile acids. In conclusion, we show that β-sitosterol and campesterol administration protected the fetus against adverse gut outcomes following UP-driven chorioamnionitis by preventing intestinal and systemic inflammation.